Serologic profiles for Sarcocystis sp. and Neospora caninum and productive performance in naturally infected beef calves - Moré, Gastón Andrés (2010)
Sarcocystis sp. and Neospora caninum infections affect cattle worldwide causing important economic losses. The objective of the present study was to trace serologic profiles for Sarcocystis sp. and N. caninum in naturally infected beef calves and analyze their relationship with transmission routes and productive performance. Samples were collected in two cow-calf operations located in Buenos Aires province, Argentina. In farm 1, 43 calves were bled and weighed three times. In farm 2, 69 calves were bled and weighed six times. Sarcocystis sp. and N. caninum immunofluorescence antibody test (IFAT) titers were averaged for each sampling point in order to trace serologic profiles for each infection. Categories were created to evaluate differences in daily weight gain. For S. cruzi antigen, animals were separated in a low-titer (≤200) and high-titer group (>200); for N. caninum, animals were grouped as infected and uninfected. Sarcocystis sp. antibody titer as well as the number of infected animals increased gradually over time in both farms. In farm 2 the low-titer group had significantly higher daily weight gain than the high-titer group. For N. caninum 44% (farm 1) and 65% (farm 2) of calves were considered infected, and the serological profile was horizontal or decreasing over time. However, seroprevalence increased in both farms and vertical and horizontal transmission frequency were estimated between 18.5%–29% and 22–25.5%, respectively. No differences were detected in daily weight gain between N. caninum groups from both farms. This is the first report of serological profiles for Sarcocystis sp. and N. caninum by IFAT in naturally infected beef calves and their relationship to different transmission routes and productive performance.